Assessment of public energy organizations’ innovation awareness and readiness for climate action : a case study of Icelandic and Kenyan energy sectors - Johannes Onjala Ochome 1981- (2022)
Due to over-reliance on fossil fuels in electricity generation, heating, and transportation, the energy sector is the largest contributor to global GHG emissions, accounting for nearly three-quarters of the 50 billion tons CO2eq of annual global GHG emissions. Developed and developing economies alike are investing in future energy solutions to meet the ever-increasing energy demand sustainably. The purpose of this study is to determine the understanding and approach to innovation in public energy organizations by investigating the internal drivers of climate action innovation. The study used quantitative research methods, such as structured self-administered, Likert scale-type online questionnaires distributed to public energy organization employees in Iceland and Kenya via QuestionPro Essentials online survey software and was analyzed using IBM SPSS Statistics version 27. The study's findings revealed that organizational innovation collaboration systems positively predicted the organization’s employee innovation awareness. Employee knowledge and skills, on the other hand, were found not to be a predictor of an organization's innovation awareness, despite the fact that theory suggests that education and training equip employees with the knowledge and skills needed to solve difficult tasks, empowering them to innovate and adapt to changing environments and markets. Furthermore, organizational innovation strategy, management structure, and leadership were discovered to be positive predictors of an organization's innovation readiness. Icelandic and Kenyan energy organizations were found to be innovating differently and, as a result, prioritizing climate action projects differently. Despite the low response rate, this study contributes to innovation research, particularly in the under-researched public sector innovation with a focus on the energy sector. Innovation, being at the heart of climate action, focuses on both technological and policy developments, and is hence key to meeting set climate action goals. ...